Implementasi Manajemen Mutu Pendidikan dalam Meningkatkan Kualitas Pembelajaran di MA Matholi`ul Huda Bugel - Muhammad Abid Robiun Nuha; Sukarman; Haryanto (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2026)
Educational quality management is commonly implemented in urban formal institutions, yet it becomes unique and challenging when applied at MA Matholi'ul Huda Bugel, which is rooted in a traditional Islamic boarding school (pesantren) environment and a religious community.This study aims to describe the implementation of educational quality management in improving learning quality at MA Matholi'ul Huda Bugel. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research subjects include the principal, vice-principal, teachers, educational staff, and students. Data analysis uses the Miles and Huberman model covering data reduction, data presentation, and conclusion drawing. The results showed that the implementation of educational quality management at MA Matholi'ul Huda Bugel is carried out through four main aspects: (1) structured and systematic learning planning; (2) improving teacher competence through training, workshops, MGMP, and academic supervision; (3) periodic learning evaluation followed by continuous improvement; and (4) strengthening quality culture through discipline, responsibility, and religious values in the madrasa environment. The principal plays a central role in building shared commitment among all educators to achieve educational quality goals. The involvement of students and parents is also a supporting factor in the success of improving learning quality.